BRANDING PRODUK EMPING MELINJO DENGAN MEMANFAATKAN WEBSITE E-COMMERCE DAN PENGGUNAAN TEKNOLOGI TEPAT GUNA MESIN SEALER/PRESS DI DESA SUKACAI - Gagah Dwiki Putra Aryono; Sigit Auliana; Asep Sapaatullah; Maman Masyhuri; Eris Dwi Purnama (Merwinspy Publisher, 2024)
Sukacai area, Pandeglang is an area in West Java that is known for its people who have skills in making emping and producing melinjo. For MSMEs, building branding is often a complex challenge. Limited resources, both in terms of finances, knowledge, and manpower, are often the main obstacle in developing an effective branding strategy. Not infrequently, MSMEs are trapped in the mindset that branding is only relevant for large companies with large budgets. In fact, proper branding can actually be the main weapon for MSMEs to compete with larger business actors. Strong branding helps MSMEs create a positive image in the eyes of consumers, build trust, and expand market reach. Manual Plastic Press is one of the appropriate technology machines that functions to cover the plastic surface of product packaging so that it gives a neat, beautiful, hygienic and non- spillable impression (making it easier to bring drinks or food for buyers), this tool uses the working principle of heating and cutting (automatic cutting), In general on the market there are manual, semi-automatic and automatic sealer machine types, What sets it apart as a whole is the way the engine operates